Pichinde Virus Infection of Outbred Hartley Guinea Pigs as a Surrogate Animal Model for Human Lassa Fever: Histopathological and Immunohistochemical Analyses - Wun-Ju Shieh; Shuiyun Lan; Sherif R. Zaki; Hinh Ly; Yuying Liang (Pathogens, 2020)
Lassa virus (LASV) is a mammarenavirus (arenavirus) that causes zoonotic infection in humans that can lead to fatal hemorrhagic Lassa fever (LF) disease. Currently, there are no FDA-approved vaccines or therapeutics against LASV. Development of treatments against LF and other related arenavirus-induced hemorrhagic fevers (AHFs) requires relevant animal models that can recapitulate clinical and pathological features of AHF diseases in humans. Laboratory mice are generally resistant to LASV infection, and non-human primates, while being a good animal model for LF, are limited by their high cost. Here, we describe a small, affordable, and convenient animal model that is based on outbred Hartley guinea pigs infected with Pichinde virus (PICV), a mammarenavirus that is non-pathogenic in humans, for use as a surrogate model of human LF. We conducted a detailed analysis of tissue histopathology and immunohistochemical analysis of different organs of outbred Hartley guinea pigs infected with different PICV strains that show differential disease phenotypes and pathologies. Comparing to infection with the avirulent PICV strain (P2 or rP2), animals infected with the virulent strain (P18 or rP18) show extensive pathological changes in different organs that sustain high levels of virus replication. The similarity of tissue pathology and viral antigen distribution between the virulent PICV–guinea pig model and lethal human LASV infection supports a role of this small animal model as a surrogate model of studying human LF in order to understand its pathogenesis and for evaluating potential preventative and therapeutic options against AHFs.